Wagner's The ring of the Nibelung - Wagner, Richard, 1813-1883.; Fisher, Burton D. (Coral Gables, Fla. : Opera Journeys, 2002)
Opera classics library explores the inner soul of Wagner's colossus of music theater. All of the Ring's mysteries are unlocked, and its immensity and complexity are analyzed and made coherent for the newcomer as well as for the seasoned enthusiast.
The Ring of the Nibelung/Opera Classics Library Series; Title Page; Contents; a prelude; The Ring of the Nibelung -- Provenance; The Rhinegold; The Valkyrie; Siegfried; Twilight of the Gods; Discography; Videography; Dictionary of Opera and Musical Terms
Discography: pages 113-121.
Videography: pages 123-128.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Wagner, Richard, -- 1813-1883.; Ring des Nibelungen (Wagner, Richard); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos